Death came with the postman : racial tensions in the military during the Vietnam War in 1969 / Carroll W. McInroe. - McInroe, Carroll W. ([publisher not identified], 2022)
A Vietnam-era, U.S. Army story of the terrible hatred generated by slavery, bigotry, and the murder of Dr. Martin Luther King.